Structural and mechanical characterization of DNA-tethered membranes on graphene - Yamamoto, Akihisa; Sakamaki, Yusuke; Abuillan, Wasim; Konovalov, Oleg; Ueno, Yuko; Tanaka, Motomu (Langmuir, 2024)
Lipid membranes that are separated from the surface of graphene by DNA tethers were prepared by surface functionalization with pyrene coupled to single-stranded DNA (ssDNA), followed by self-assembly of the mixture of ssDNA-functionalized phospholipid and the matrix phospholipids. The formation of uniform membranes was confirmed by fluorescence microscopy, and the structures of the systems before and after hybridization in the direction perpendicular to the global plane of the membranes were investigated using high-energy X-ray reflectivity. The thickness values of the DNA spacers (15 and 37 bp) calculated from the best-fit results were less than the expected thicknesses of the double-stranded DNA (dsDNA) chains taking the upright conformation, indicating that the DNA spacers are tilted with respect to the direction normal to the surface. The Young’s moduli of the DNA-tethered membranes obtained by AFM nanoindentation showed higher values than the membranes with no DNA tethers, which suggests that the DNA layer resists against the compression, lifting up the membrane. Intriguingly, the presence of DNA tethers caused no increase in the yield depth. The smaller thickness values as well as the unchanged yield depth suggest that the dsDNA chains can tilt and rotate, which can be attributed to the flexible pyrene-DNA junction.
Gesehen am 16.12.2024